Glafki Gotsi, Androniki Dialeti and Eleni Fournaraki (eds.), Το φύλο στην ιστορία: αποτιμήσεις και παραδείγματα [Gender in history: historiographical accounts and case studies] - Karydaki, Danae (Historein, 2018)
Review of Glafki Gotsi, Androniki Dialeti, Eleni Fournaraki (eds.), Το φύλο στην ιστορία: αποτιμήσεις και παραδείγματα [Gender in history: historiographical accounts and case studies]. Athens: Asini, 2015, 373 pp.